Immediate changes in pressure pain sensitivity after thoracic spinal manipulative therapy in patients with subacromial impingement syndrome: A randomized controlled study. Issue 4 (August 2015) - Kardouni, Joseph R.; Shaffer, Scott W.; Pidcoe, Peter E.; Finucane, Sheryl D.; Cheatham, Seth A.; Michener, Lori A.
Abstract Background Thoracic SMT can improve symptoms in patients with subacromial impingement syndrome. However, at this time the mechanisms of SMT are not well established. It is possible that changes in pain sensitivity may occur following SMT. Objectives To assess the immediate pain response in patients with shoulder pain following thoracic spinal manipulative therapy (SMT) using pressure pain threshold (PPT), and to assess the relationship of change in pain sensitivity to patient-rated outcomes of pain and function following treatment. Design Randomized Controlled Study. Methods Subjects with unilateral subacromial impingement syndrome (n = 45) were randomly assigned to receive treatment with thoracic SMT or sham thoracic SMT. PPT was measured at the painful shoulder (deltoid) and unaffected regions (contralateral deltoid and bilateral lower trapezius areas) immediately pre- and post-treatment. Patient-rated outcomes were pain (numeric pain rating scale – NPRS), function (Pennsylvania Shoulder Score – Penn), and global rating of change (GROC). Results There were no significant differences between groups in pre-to post-treatment changes in PPT (p ≥ 0.583) nor were there significant changes in PPT within either group (p ≥ 0.372) following treatment. NPRS, Penn and GROC improved across both groups (p < 0.001), but there were no differences between the groups (p ≥ 0.574). Conclusion There were no differences in pressure pain sensitivity between participants receiving thoracic SMT versus sham thoracic SMT. Both groups had improved patient-rated pain and function within 24–48 h of treatment, but there was no difference in outcomes between the groups.